2009
DOI: 10.1161/strokeaha.108.535146
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Patients at High Risk for Poor Outcome After Intra-Arterial Therapy for Acute Ischemic Stroke

Abstract: Background Intra-arterial recanalization therapy (IAT) is increasingly utilized for acute stroke. Despite high rates of recanalization the outcome is variable. We attempted to identify predictors of outcome that will enable better patient selection for IAT. Methods All patients who underwent IAT at the UT Houston Stroke Center were reviewed. Poor outcome was defined as modified Rankin Scale score 4–6 on hospital discharge. Findings were validated in an independent dataset of 175 patients from UCLA Stroke Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(118 citation statements)
references
References 19 publications
(23 reference statements)
3
113
1
1
Order By: Relevance
“…When DM was replaced in the above analyses with admission hyperglycemia (glucose Ͼ 150 mg/dL 9 ) the results were not substantially altered (data not shown).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…When DM was replaced in the above analyses with admission hyperglycemia (glucose Ͼ 150 mg/dL 9 ) the results were not substantially altered (data not shown).…”
Section: Resultsmentioning
confidence: 94%
“…Because other studies have found that hyperglycemia on initial glucose measurement at acute stroke presentation is associated with poor outcome after endovascular stroke treatment, 9 we also examined whether admission hyperglycemia yielded different results from a history of DM. When DM was replaced in the above analyses with admission hyperglycemia (glucose Ͼ 150 mg/dL 9 ) the results were not substantially altered (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers from Houston and UCLA developed the HIAT score, which is composed of 3 factors found to be significant and independent predictors of patient outcome subsequent to IAT regardless of patient recanalization status: age, NIHSS score, and admission glucose level. 26 Patients treated with IAT at the University of Texas Houston Stroke Center were retrospectively assigned 1 point for each of the following factors: age > 75 years, NIHSS score > 18, and glucose level > 150 mg/dl. The median NIHSS score for good outcome was 16, while the median NIHSS score for poor outcome was 20.…”
Section: Existing Predictive Scoring Systemsmentioning
confidence: 99%
“…As previously mentioned, the authors of the HIAT study found that the median baseline NIHSS score for patients with good outcomes after IAT was 16, while the median baseline NIHSS score for poor outcomes was 20; the rate of recanalization did not differ significantly between the good and poor outcome groups (p = 0.4). 26 The THRIVE score author group trichotomized NIHSS scores (≤ 10, 11-20, and ≥ 21) and concluded that the breakdown of the scale could effectively predict those very likely, moderately likely, and least likely to experience good outcome subsequent to endovascular stroke treatment, respectively. 20 Yet another analysis reports that patients who experienced futile recanalization, defined as successful removal of the thrombus without corresponding clinical improvement, had higher median baseline NIHSS scores (19) compared with those with nonfutile recanalization pursuant to IAT (14).…”
Section: Individual Predictors Of Futile Recanalizationmentioning
confidence: 99%